Answer:
t^-12
Step-by-step explanation:
you multiply the -2 and 6.
Answer:
(C) 2√15
Step-by-step explanation:
Recognize that all the triangles are right triangles, so are similar to each other. In these similar triangles, the ratio of the short side to the long side is the same for all.
... CB/CA = CT/CB
... CB² = CA·CT = 10·6 = 60 . . . . . . . . . . multiply by CA·CB; substitute values
... CB = √60 = 2√15 . . . . . . . take the square root; simplify
_____
<em>Comment on this solution</em>
The altitude to the hypotenuse of a right triangle (CB in this case) divides the hypotenuse into lengths such that the altitude is their geometric mean. That is ...
... CB = √(AC·CT) . . . . as above
This is true for any right triangle — another fact of geometry to put in your list of geometry facts.
Answer:
Step-by-step explanation:
Corresponding angles of both the squares are congruent. (angles of a square measure 90°)
Ratio of the sides of the given squares = ![\frac{\text{Side length of small square}}{\text{Side length of the large square}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ctext%7BSide%20length%20of%20small%20square%7D%7D%7B%5Ctext%7BSide%20length%20of%20the%20large%20square%7D%7D)
= ![\frac{2}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7D)
This ratio of side lengths is constant for all corresponding sides.
Therefore, corresponding sides are proportional.
Since, all angles of both the squares are congruent and all the sides are proportional, both the squares will be similar.
Scale factor = ![\frac{\text{Side length of large square}}{\text{Side length of the smaller square}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ctext%7BSide%20length%20of%20large%20square%7D%7D%7B%5Ctext%7BSide%20length%20of%20the%20smaller%20square%7D%7D)
= ![\frac{5}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2%7D)
= 2.5
This sequence of similarity transformations shows the figures are similar.
Answer:
2x-3
Step-by-step explanation:
f(x) = 3x-1
g(x) = x+2
Find (f-g)(x), this means we need to subtract g from x.
(3x-1) - (x+2)
Subtract the like terms:
3x -x = 2x
-1 -2 = -3
Combine them to get 2x-3
Answer:
1 = No 2 = Yes 3 = 1.88
Step-by-step explanation: